The CHD remodeling factor Hrp1 stimulates CENP-A loading to centromeres - Walfridsson, Julian (Oxford University Press, 2005)
Centromeres of fission yeast are arranged with a central core DNA sequence flanked by repeated sequences. The centromere-associated histone H3 variant Cnp1 (SpCENP-A) binds exclusively to central core DNA, while the heterochromatin proteins and cohesins bind the surrounding outer repeats. CHD (chromo-helicase/ATPase DNA binding) chromatin remodeling factors were recently shown to affect chromatin assembly in vitro. Here, we report that the CHD protein Hrp1 plays a key role at fission yeast centromeres. The hrp1Δ mutant disrupts silencing of the outer repeats and central core regions of the centromere and displays chromosome segregation defects characteristic for dysfunction of both regions. Importantly, Hrp1 is required to maintain high levels of Cnp1 and low levels of histone H3 and H4 acetylation at the central core region. Hrp1 interacts directly with the centromere in early S-phase when centromeres are replicated, suggesting that Hrp1 plays a direct role in chromatin assembly during DNA replication.